The Moral Origins of God: Darwin, Durkheim, and the Homo Duplex Theory of Theogenesis - Marshall, Douglas A. (Frontiers in Sociology, 2016)
A socio-evolutionary theory of the origin of “God” is presented. Its starting point is behavioral duplexity, the fact that human beings are subject to two parallel modes of behavioral control: an older nonconscious system, and a newer conscious one. The theory posits that the fabrication of, and subsequent belief in, supernatural entities (“Gods”) is a predictable byproduct of the interaction of these two systems. Specifically, because human beings’ profoundly social and moral faculties are primarily nonconscious, individuals experience their functioning as an external and coercive moral force. Faced with the conscious mode’s need to maintain the integrity of its nomos by accounting for such experiences, individuals collectively confabulate corresponding external, coercive, and moral entities, to which they misattribute this force. In doing so, they effectively create, and re-create, their “god(s)”.